Wicked cool PHP : real-world scripts that make difficult things possible - Steinmetz, William (No Starch Press, 2008)
PHP is an easy-to-use scripting language perfect for quickly creating the Web features you need. Once you know the basics of how the language works, wouldn't it be great to have a collection of useful scripts that solve those tricky problems and add interesting functionality to your site? We thought so, too. Instead of starting at "Hello World," Wicked Cool PHP assumes that you're familiar with the language and jumps right into the good stuff. After you learn the FAQs of life-the most commonly wished for PHP scripts-you'll work your way through smart configuration options and the art of forms, all the way through to complex database-backed scripts. Wicked Cool PHP contains a wide variety of scripts to process credit cards, check the validity of email addresses, template HTML, and serve dynamic images and text. The 76 easily implemented scripts will also teach you how to: Send and receive email notifications Track your visitors' behavior with cookies and sessions Override PHP's default settings Manipulate dates, images, and text on the fly Harness SOAP and other web services Create an online poll, ecard delivery system, and blog But it's not all fun and games: Security is a big concern when programming any web application. So you'll learn how to encrypt your confidential data, safeguard your passwords, and prevent common cross-site-scripting attacks. And you'll learn how to customize all of the scripts to fit your own needs. Dynamic Web content doesn't have to be difficult. Learn the secrets of the craft from two experienced PHP developers with Wicked Cool PHP .